MULTIMODAL STRATEGIES OF MODERATE ISLAMIC DIGITAL DA’WAH ON THE RUKUN INDONESIA YOUTUBE CHANNEL (Harmoni, 2025)
This study examines how the Rukun Indonesia YouTube channel constructs representations of moderate Islam through multimodal digital da’wah. Although research on online Islamic communication has expanded, few studies analyze how moderate Islamic values are articulated through integrated visual, verbal, and auditory modes, particularly within interfaith contexts. This study addresses this gap by investigating how multimodal strategies shape public perceptions of inclusive Islam. This study employed a descriptive qualitative design using 25 purposively selected podcast videos uploaded between 2022 and 2025. Data consisted of spoken narratives, visual imagery, symbolic elements, background music, and audience comments. Multimodal Discourse Analysis was used to interpret meaning-making across modes, supported by thematic coding of narrative structures and audience responses. The findings indicate that: First, humanitarian narratives and empathetic visual framing function as the primary vehicles for communicating moderate Islamic values. Second, symbols of cultural and religious diversity embedded in visual and musical elements reinforce messages of tolerance and coexistence. Third, audience responses indicate strong emotional engagement and broad acceptance from both Muslim and non-Muslim viewers, suggesting that multimodal da’wah can effectively foster interfaith understanding. These results demonstrate that digital da’wah can operate as a participatory and dialogic space that counters polarizing religious discourse. The study concludes that multimodal strategies offer significant potential for strengthening inclusive Islamic communication and recommends further research on cross-platform comparative models of moderate digital da’wah. AbstrakPenelitian ini mengkaji bagaimana kanal YouTube Rukun Indonesia membangun representasi Islam moderat melalui dakwah digital multimodal. Meskipun kajian mengenai komunikasi Islam daring terus berkembang, masih sedikit penelitian yang menganalisis bagaimana nilai-nilai Islam moderat diartikulasikan melalui integrasi mode visual, verbal, dan auditori, khususnya dalam konteks lintas iman. Studi ini mengisi kekosongan tersebut dengan meneliti bagaimana strategi multimodal membentuk persepsi publik terhadap Islam yang inklusif. Penelitian ini menggunakan desain kualitatif deskriptif dengan menganalisis 25 video podcast yang dipilih secara purposif dan diunggah antara 2022 hingga 2025. Data mencakup narasi lisan, citra visual, elemen simbolik, musik latar, serta komentar audiens. Analisis Wacana Multimodal digunakan untuk menafsirkan proses pembentukan makna lintas mode, didukung oleh pengodean tematik terhadap struktur naratif dan respons penonton. Hasil penelitian menunjukkan tiga pola utama. Pertama, narasi kemanusiaan dan framing visual yang empatik menjadi sarana utama dalam menyampaikan nilai-nilai Islam moderat. Kedua, simbol keberagaman budaya dan agama yang tertanam dalam elemen visual dan musikal memperkuat pesan toleransi dan koeksistensi. Ketiga, respons audiens menunjukkan keterlibatan emosional yang kuat dan penerimaan luas dari penonton Muslim maupun non-Muslim, yang mengindikasikan bahwa dakwah multimodal efektif dalam mendorong pemahaman lintas iman. Temuan ini menunjukkan bahwa dakwah digital dapat berfungsi sebagai ruang dialogis dan partisipatif yang mampu menandingi wacana keagamaan yang memecah belah. Penelitian ini menyimpulkan bahwa strategi multimodal memiliki potensi signifikan dalam memperkuat komunikasi Islam yang inklusif dan merekomendasikan penelitian lanjutan mengenai model perbandingan dakwah digital moderat lintas platform.
Keywords: Moderate Islam; Digital Da’wah; Multimodal Discourse Analysis (MDA); Youtube Communication; Audience Reception